Webmap Application Training As An Effort For Flood Mitigation In The Agricultural Sector In Dlanggu Village, Lamongan Regency, East Java, Indonesia - Mala Rosa Aprillya; Uswatun Chasanah; Mufti Ari Bianto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Natural conditions are increasingly uncertain and difficult to predict due to changes in rainfall patterns and climate. Excessive rainfall can cause flooding which is detrimental to the agricultural sector. Flooding is a natural challenge that is often faced in the agricultural sector. This challenge is faced by most of the agricultural land in Lamongan Regency, including in Dlanggu Village. The impact of flooding on rice fields in certain locations which is increasingly widespread and intensive from year to year has caused considerable losses for farmers. The purpose of this activity is to map flood-affected agricultural land in a participatory manner with the help of the WebMap application. The method of implementing this activity includes the preparation stage, implementation stage, and monitoring and evaluation stage. The results of the activity showed that participants were very enthusiastic about this activity program, as evidenced by the positive response in the form of the presence of 96% of the training participants and active discussion activities during the socialization and training took place. After the training, the participants also expected a follow-up in the form of assistance from the service team to improve skills with WebMap applications in other fields. This activity is expected to be a solution that can be offered to provide an early warning system based on mapping so that the delivery of information about floods can be conveyed more quickly to the community, especially people who have agricultural livelihoods to be aware of flood disasters.